The Impact of Covid-19 on Online Learning Activities at The University of The Helvetia Medan Health Institute - Indra Ginting; Asriwati Asriwati; Ismail Effendy; Tiwanto Dakhi (Newinera Publisher, 2020)
COVID-19 is a disease outbreak that originated in China that is spreading rapidly throughout the world. COVID-19 spread in Indonesia in mid-March 2020. The spread of this virus caused losses to many countries, especially in the economic sector. In the field of education, COVID-19 also drastically changes the learning model; All learning activities are carried out online, starting from elementary school to university level. This research is a qualitative descriptive study that describes online learning activities at the Helvetia Institute of Health after it has been determined that all learning activities are carried out at home using online mode. The subjects consisted of 4 students and 3 lecturers at the Helvetia Institute of Health. Data collection using interviews. Based on the results of interviews, online learning activities at the Helvetia Institute of Health have been effective by using the Zoom, Google Classroom, Schoology, Webex, E-Learning, WhatsApp, and Cloux applications. Obstacles in the implementation of online learning are the problem of internet connection and inadequate economy.